From rebellion to riots collective violence on Indonesian Borneo - Davidson, Jamie Seth 1971- (New perspectives in Southeast Asian studies, 2009)
From Rebellion to Riots examines contemporary violence in one of Indonesia's most heterogeneous provinces, West Kalimantan. It documents how a communist rebellion in the 1960s and low-level conflicts in the decades that followed led to major ethnic clashes in the late 1990s, when an indigenous empowerment movement took shape and local elites sought to capture the benefits of decentralization and democratization